Body composition and population regulation of Svalbard reindeer - Reimers, Eigil (Rangifer, 1984)
After severe winters, body weight, fat, and lean tissue of the high Arctic Svalbard reindeer may be reduced by 50, 90-97 and 30-40% respectively. Absence of harassment from predators, insects and man allows surviving animals to rapidly restore body reserves during the summer. That accumulation of large pre-winter body reserves is essential, as the reindeer's survival and population control is dependant upon use of winter forage which is resistant to grazing but poor in quality.Kroppssammensetning og bestandsregulering hos svalbardrein.Abstract in Norwegian / Sammendrag: Etter harde vintre kan kroppsvekt, fett og magert vev bli redusert med henholdsvis 50, 90 - 97% henholdsvis. Fravær av forstyrrelser av rovdyr, insekter og mennesker tillater overlevende dyr å fornye sine kroppsreserver raskt gjennom sommeren. Denne akkumulering av store kroppsreserver før vinteren er livsviktig, da reinens overlevelse og bestandskontroll er avhengig av et vinterfor som er motstandsdyktig mot beiting, men er av dårlig kvalitet.Huippuvuorten porojen ruumiinkokoonpano ja eläinkannan säätö.Abstract in Finnish /Yhteenveto: Ankarien talvien jälkeen voi ruumiinpaino, rasva ja laiha kudos vähetä 50, 90-97 ja 30-40 % jokainen erikseen. Petoeläinten, hyönteisten ja ihmisten häiriöiden poisjäädessä on eloonjääneillä eläimillä mahdollisuus uusia nopeasti ruumiin vara-aineet kesän kuluessa. Tamä suurien ruumiin vara-aineiden kasaantuma ennen talvea on elintärkeä, koska porojen eloonjääminen ja eläinkannan valvonta on riippuvainen talvilaitumesta, joka sietää laiduntamisen, vaikka se on huonoa laatua.